Computed Tomographic Evaluation of Mandibular Ameloblastoma - N Eswar; N Gnanasundaram (Wolters Kluwer Medknow Publications, 2003)
Computed tomography is an advanced tomographic technique in which a particular section of the body which has to be imaged is reconstructed with the aid of computer technology. Computed tomography is applied in the field of oral diagnosis in the evaluation of tumors and traumatic conditions of maxillofacial region particularly to assess the soft tissue involvement in these conditions, to establish the contents within a lesion and to determine the vascularity through intravenous contrast studies. Five interesting cases of mandibular ameloblastoma are presented here, each case showing different histological pattern and corresponding computer tomographic appearance. Also an attempt is made to establish CT pattern in these histological varieties of ameloblastoma.